Impact of prior smoking exposure and COPD comorbidity on treatment response to monoclonal antibodies in patients with severe asthma. Issue 3 (16th August 2021) - Morobeid, Heba; Pizarro, Carmen; Biener, Leonie; Ulrich-Merzenich, Gudrun; Kütting, Daniel; Nickenig, Georg; Skowasch, Dirk
Despite the prognostic role of smoking in asthma [1], clinical studies of asthma usually exclude current smokers or ex-smokers with a smoking history of >10 pack-years [2–5]. Specifically, the role of humanised monoclonal antibody therapy in patients with severe asthma and prior smoking exposure has not been studied; however, these drugs are used in patients with severe asthma and a history of smoking [6–9]. The aim of the present study was to evaluate in a real-world setting how a history of smoking and comorbid COPD affect the clinical outcome of patients suffering from severe asthma that are treated with monoclonal antibodies. Patients suffering from severe asthma may benefit from an antibody treatment irrespective of their status as an ex-smoker https://bit.ly/3fYC8tC